The Effect of Pulley Training on Leg Muscle Power in Swimming Athletes at the Bekasi Olympic Aquatic Club, Bekasi Regency - Putra Septian; Mia Kusumawati (Universitas Negeri Semarang, 2025)
Leg muscle power is a crucial physical component for swimmers, determining initial acceleration during starts and turns. This study explicitly analyzed the effect of a structured pulley training program on the leg muscle power of 30 swimmers at the Bekasi Olympic Aquatic Club, where limitations in this area were previously identified. Using a quasi-experimental, one-group pre-test-post-test design, athletes underwent a 14-day combined land and water pulley training intervention. Leg power was directly measured via Vertical Jump (VJ), while its functional impact was measured by 50-meter butterfly swim time. A Paired-Samples T-Test revealed two significant outcomes: first, a highly significant increase in leg power, evidenced by a 2.30 cm average increase in VJ height (t(29) = -8.460, p < .001); and second, a highly significant improvement in swim performance (t(29) = 6.565, p < .001). It is concluded that pulley training is a valid and effective intervention. These dual findings provide strong empirical evidence for coaches to implement this program to optimize athletes' fundamental physical capabilities and directly enhance competitive performance